EXECUTIVE SUMMARY: GETTING CLOSE TO THE CUSTOMER. Issue 3 (10th September 2013) - Fisman, Raymond; Paravisini, Daniel; Vig, Vikrant
Abstract : Raymond Fisman, Daniel Paravisini, Vikrant Vig, "Cultural Proximity and Loan Outcomes", National Bureau of Economic Research Working Paper 18096.